2012
DOI: 10.1103/physrevd.85.123531
|View full text |Cite
|
Sign up to set email alerts
|

Fluid/gravity duality with Petrov-like boundary condition in a spacetime with a cosmological constant

Abstract: Recently it has been shown that imposing Petrov-like condition on the boundary may reduce the Einstein equation to the Navier-Stokes equation in the non-relativistic and near-horizon limit.In this paper we extend this framework to a spacetime with a cosmological constant. By explicit construction we show that the Navier-Stokes equation can be derived from both black brane background and spatially curved spacetime. We also conjecture that imposing Petrov-like condition on the boundary should be equivalent to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 50 publications
6
23
0
Order By: Relevance
“…Another instance of the fluid/gravity correspondence in asymptotically flat spacetimes can be found in the blackfold approach [17,18]. Further developments were reported in [19][20][21][22][23][24][25][26][27][28].…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…Another instance of the fluid/gravity correspondence in asymptotically flat spacetimes can be found in the blackfold approach [17,18]. Further developments were reported in [19][20][21][22][23][24][25][26][27][28].…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…[22][23][24] to a spacetime with a matter field. We have demonstrated that with the help of the Petrov-like condition and Einstein-Maxwell constraints, the incompressible Navier-Stokes equation can be derived for a charged fluid living on the cutoff surface which is embedded into a charged AdS black brane, an RN-AdS black p ðT n n þ 2Ã þ T þ T 00 À 2T 0 n Þ i j À T i…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In Ref. [24], the holographic nature of the Petrov-like condition was further disclosed in a spacetime with a cosmological constant. Based on all the work above, it is reasonable to conjecture that in the approach of fluid/ gravity duality, imposing the Petrov-like condition on the cutoff surface is equivalent to imposing the regularity condition on the future horizon at least in the near-horizon limit.…”
Section: Introductionmentioning
confidence: 98%
“…This cut-off surface approach has been applied in various cases, see [12][13][14]. For example, it was extended for higher curvature gravity theories [15][16][17][18][19] as well as for the AdS [20,21] and dS [22] gravity theories (for other theories, like black branes, see [23]). Very recently, two of the authors of this paper showed in [13] that an incompressible DNS-like equation can be obtained in the cut-off surface approach.…”
Section: Introductionmentioning
confidence: 99%